A Study on the Constraints Encountered By Quantity Surveyors In The Process Of Preparation of Interim Payment - Tan, Sophia Siok Hooi; Masidah, Abdul Majid; Nurul Huda, Ahamad (2016)
Periodic payments to contractors are essential parts in construction contractual arrangement. Interim payments made on time will greatly assist contractors to overcome cash flow problem and provide source of self-financing in respect of their own commitments to suppliers and sub-contractors. However, there remains a chronic problem of delayed payment to the contractors in the construction industry of Malaysia that is affecting the entire delivery chain. The main purpose of the present study is to identify the constraints encountered by Quantity Surveyors (QS) who work in consultant firms in the process of preparation of interim payment certificate which may lead to delay in the issuance of payment. In addition, recommendations for appropriate solutions to reduce the constraints were also established. A questionnaire survey was conducted to solicit the opinions of QS who work in consultant firms located in the Klang Valley. In total, there is 41 respondents participated in the survey. Results obtained from the questionnaire survey were analysed using descriptive statistics method. From the analysis, five most important constraints that may lead to delay in the issuance of interim payments have been identified which are (1) Sufficiency of adequate supporting documents; (2) time available for valuation and certification; (3) errors in submitting claims (4) dispute on quantity of work done and (5) trust and faith relationship between parties. From this study, five types of recommendation to reduce the constraints were also highlighted which include (1) reducing workload; (2) compliance of term of contract on the part of contractors; (3) improvement on claim submission; (4) discussion before submission and (5) development of trust and faith between the QS and contractors. It can be concluded that the process of issuance of interim payment can be expedite should there is an effort to address the constraints faced by the QS.